Produksi dan Pemasaran Kelinci Pedaging : Sebuah Tinjauan Sistematis - Rayhan Ananta; Mahayu Mawar Kalista; Zaqia Yuliana Pratiwi; Wien Kuntari (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
The productivity of meat rabbits in producing meat is higher than beef livestock. Meat rabbits are also an alternative source of animal protein that can be utilized by the Indonesian people. Rabbits have great potential to be developed in Indonesia. The aim of this writing is, among other things, to determine the effective level of productivity for meat rabbits and the sustainability of the rabbit market share which will be well supported by good marketing strategies, actors, marketing channels so that the competitiveness of rabbit meat commodities can be competitive and innovative with competing commodities. This systematic review of identification of national and international articles is divided into 2 clusters with production and marketing. The results of the discussion from this article for effective product quality need to pay attention to seeds, feed, and also cages and for marketing there are several patterns of marketing actors who carry out planning and determining prices and distribution of meat rabbits.